A high adhesion glass fiber sizing and its preparation method
Patent Information
- Application Number
- CN202610778699.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-02
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-06-02
AI Technical Summary
[0002]玻璃纤维是复合材料领域应用广泛的增强基材,浸润剂作为玻璃纤维表面处理的核心助剂,直接影响玻璃纤维的成膜效果、界面结合能力及复合材料的整体使用性能;当前行业内主流玻璃纤维浸润剂多采用单一成膜物质、单一种类偶联剂与常规无机填料简单复配,加工方式以常规一次性混合为主,各功能组分难以形成有效协同
1、本发明采用双组分成膜剂复配,可在玻璃纤维表面形成均匀完整的膜层,弥补膜层微观缺陷,提升玻璃纤维的耐磨与防护性能;双硅烷偶联剂协同作用,实现玻璃纤维与树脂基体的双向界面键合,强化界面结合效果,避免复合材料使用时的界面分离问题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of glass fiber surface treatment additives, specifically to a high-adhesion glass fiber wetting agent and its preparation method. Background Technology
[0002] Glass fiber is a widely used reinforcing substrate in the field of composite materials. As the core auxiliary agent for glass fiber surface treatment, the impregnating agent directly affects the film-forming effect, interfacial bonding ability and overall performance of the composite material. Currently, most mainstream glass fiber impregnating agents in the industry use a simple compounding of a single film-forming substance, a single type of coupling agent and conventional inorganic filler. The processing method is mainly conventional one-time mixing, and it is difficult for the functional components to form an effective synergy.
[0003] Existing sizing agents generally suffer from insufficient film density, and the film layer is prone to microscopic defects, failing to provide continuous and stable physical protection for glass fibers; single coupling agents can only achieve unidirectional interfacial bonding, and the bonding effect between glass fibers and resin matrix is limited, making the composite material prone to interfacial detachment during use.
[0004] In conventional systems, nanofillers are prone to agglomeration and poor dispersion uniformity, which not only fails to optimize film performance but also reduces the overall stability of the system. At the same time, existing wetting agents have weak resistance to environmental aging, and their mechanical properties degrade significantly under complex working conditions. They are also prone to problems such as stratification and precipitation during storage, affecting the actual use effect.
[0005] In addition, commercially available products struggle to balance preparation costs and overall performance. Low addition levels result in incomplete film formation and a significant drop in performance, while high addition levels increase production costs, making them unsuitable for industrial-scale production needs. Summary of the Invention
[0006] The primary objective of this invention is to provide a high-adhesion glass fiber impregnating agent and its preparation method.
[0007] A further objective of this invention is to provide a high-adhesion glass fiber sizing agent, comprising the following components by mass percentage: 4.74%-14.67% aqueous polyurethane emulsion, 5.26%-7.4% hydroxyl-modified acrylic emulsion, 0.74%-2.89% aminosilane coupling agent, 1.06%-1.61% epoxysilane coupling agent, 0.5%-2.1% modified nano-silica, 0.3%-0.8% composite wetting and dispersing agent, 0.08%-0.18% defoamer, 0.05%-0.1% preservative, and 70.42%-81.57% deionized water, wherein the total mass percentage of all components is 100%. The aqueous polyurethane emulsion is an industrial-grade anionic aqueous polyurethane film-forming emulsion with a solid content of 30%-35%; the hydroxyl-modified acrylic emulsion is an industrial-grade hydroxyl-containing acrylic copolymer emulsion with a solid content of 40%-45%; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the epoxysilane coupling agent is γ-glycidoxypropyltrimethoxysilane; and the modified nano-silica is a hydrophilic silane surface-modified powder with a particle size of 20nm-80nm. The composite wetting and dispersing agent is formulated from polyether nonionic surfactants and carboxylic acid anionic dispersants; the defoamer is a polyether defoamer specifically for water-based systems; the preservative is an isothiazolinone preservative specifically for water-based coatings; and the conductivity of the deionized water is not higher than 20 μS / cm.
[0008] Preferably, the waterborne polyurethane emulsion has a mass percentage of 11.1%-14.67%, and the hydroxyl-modified acrylic emulsion has a mass percentage of 7.33%-7.4%.
[0009] Preferably, the aminosilane coupling agent has a mass percentage of 1.75%-2.89%, and the epoxysilane coupling agent has a mass percentage of 1.45%-1.61%.
[0010] Preferably, the modified nano-silica has a mass percentage of 1.2%-2.1%.
[0011] A method for preparing a high-adhesion glass fiber sizing agent includes the following steps performed in sequence: preparation of base liquid, pre-dispersion treatment of additives, uniform dispersion of nanoparticles, stepwise hydrolysis and activation of coupling agent, low-temperature and low-speed composite emulsification of film-forming agent, and blending, filtration and curing. The base solution was prepared by adding deionized water to the reactor, maintaining a constant temperature in a water bath, and then starting the stirring. The pre-dispersion treatment of the additives involves sequentially adding a composite wetting and dispersing agent, an antifoaming agent, and a preservative to the base liquid, and stirring until the dispersion is uniform. The nanoparticles are uniformly dispersed: modified nano-silica is added to the system and dispersed at high speed until the powder is uniform and free of agglomeration; The coupling agent is activated by stepwise hydrolysis: first, an aminosilane coupling agent is added dropwise and stirred for activation; then, an epoxysilane coupling agent is added dropwise and stirred at a constant temperature for activation. The film-forming agent undergoes low-temperature, low-speed composite emulsification: water-based polyurethane emulsion and hydroxyl-modified acrylic emulsion are added dropwise to the system in sequence, and the mixture is stirred at low temperature and low speed until the composite emulsification is complete. The blending, filtration, and maturation process involves stirring and blending the system, filtering it, and then sealing it for standing maturation.
[0012] Preferably, the process conditions for preparing the base liquid are: constant water bath temperature of 38℃-40℃, stirring speed of 340r / min-380r / min, and stirring time of 6min.
[0013] Preferably, the process conditions for uniformly dispersing the nanoparticles are: dispersion speed of 610 r / min-680 r / min and dispersion time of 18 min.
[0014] Preferably, the process conditions for the stepwise hydrolysis and activation of the coupling agent are: a total dropwise addition time of 10 min for the coupling agent and a constant temperature activation and stirring time of 35 min.
[0015] Preferably, the process conditions for low-temperature and low-speed composite emulsification of the film-forming agent are: stirring speed of 340 r / min-380 r / min and stirring time of 30 min.
[0016] Preferably, the maturation time for the blending and filtration maturation is 2 hours.
[0017] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention uses a two-component film-forming agent compound to form a uniform and complete film layer on the surface of glass fiber, which can make up for the micro-defects of the film layer and improve the wear resistance and protective performance of glass fiber; the synergistic effect of the bissilane coupling agent realizes the bidirectional interfacial bonding between glass fiber and resin matrix, strengthens the interfacial bonding effect, and avoids the problem of interfacial separation when the composite material is used.
[0018] 2. The modified nanofiller of this invention is uniformly dispersed in the system, further optimizing the film structure, improving the product's resistance to environmental aging, and extending the service life of the composite material; the compound wetting and dispersing agent ensures the compatibility and stability of each component, and the step-by-step emulsification and activation process enables the functional components to be fully activated and compounded, eliminating problems such as system stratification and precipitation, and greatly improving the product's storage stability.
[0019] 3. The raw materials used in this invention are all general industrial raw materials, with stable sources and no special pretreatment required. They can be directly purchased and fed into the production line, making them suitable for continuous industrial production. This invention improves the interfacial bonding strength, film quality, and environmental adaptability of glass fibers, solving the problems of single performance, poor stability, and insufficient adaptability of existing sizing agents, and has high industrial application value. Detailed Implementation
[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] All raw materials used in this invention are commercially available general industrial raw materials, which can be obtained through open procurement from domestic chemical raw material manufacturers. The raw material specifications are clear and the source is stable, and those skilled in the art can directly purchase and replicate them.
[0022] The waterborne polyurethane emulsion is an industrial-grade anionic waterborne polyurethane film-forming emulsion with a solid content of 30%-35%, which is suitable for waterborne glass fiber impregnating systems. The hydroxyl-modified acrylic emulsion is made from industrial-grade hydroxyl-containing acrylic copolymer emulsion with a solid content of 40%-45%, and has the characteristics of forming film at room temperature and crosslinking at high temperature. The aminosilane coupling agent selected is industrial grade γ-aminopropyltriethoxysilane; the epoxysilane coupling agent selected is industrial grade γ-glycidoxypropyltrimethoxysilane. Modified nano-silica is a hydrophilic silane surface-modified powder with a particle size of 20nm-80nm, and is an industrial standard. The composite wetting and dispersing agent is composed of industrial-grade polyether nonionic surfactants and carboxylic acid anionic dispersants. The defoamer is a polyether defoamer specifically for water-based systems; the preservative is an isothiazolinone preservative specifically for water-based coatings. The dispersion medium is industrial deionized water with a conductivity not exceeding 20 μS / cm.
[0023] The wetting agent of this invention is prepared by a stepwise emulsification and activation process. The overall process flow is divided into 6 fixed stages: base liquid preparation, auxiliary agent pre-dispersion treatment, uniform dispersion of nanoparticles, stepwise hydrolysis and activation of coupling agent, low-temperature and low-speed composite emulsification of film-forming agent, and blending, filtration and maturation.
[0024] Each embodiment adopts a standardized preparation process, with only minor adjustments to the component ratios and corresponding process parameters based on formulation requirements.
[0025] All samples were cured using a standard drying process at a temperature of 125°C for 15 minutes to ensure complete cross-linking and film formation of the wetting agent, thus meeting the requirements for test reproducibility and consistency with industrial production.
[0026] Example 1:
[0027] This embodiment provides a high-adhesion glass fiber impregnating agent. The components, by mass percentage, are as follows: 11.1% aqueous polyurethane emulsion, 7.4% hydroxyl-modified acrylic emulsion, 1.75% aminosilane coupling agent, 1.45% epoxysilane coupling agent, 1.2% modified nano-silica filler, 0.8% composite wetting and dispersing agent, 0.18% defoamer, 0.1% preservative, and 76.02% deionized water. The total mass percentage of all components is 100%.
[0028] The preparation process parameters were set as follows: water bath constant temperature 40℃, base liquid stirring speed 380r / min, stirring time 6min, nanofiller high-speed dispersion speed 680r / min, dispersion time 18min, composite silane coupling agent dropwise addition time 10min, constant temperature activation stirring 35min, film-forming agent dropwise stirring speed 380r / min, stirring time 30min, and maturation time 2h.
[0029] Example 2:
[0030] This embodiment provides a high-adhesion glass fiber impregnating agent. The components, by mass percentage, are as follows: 14.67% aqueous polyurethane emulsion, 7.33% hydroxyl-modified acrylic emulsion, 1.75% aminosilane coupling agent, 1.45% epoxysilane coupling agent, 1.2% modified nano-silica filler, 0.8% composite wetting and dispersing agent, 0.18% defoamer, 0.1% preservative, and 72.62% deionized water. The total mass percentage of all components is 100%.
[0031] The preparation process parameters in this embodiment are completely consistent with those in Example 1. Only the ratio of the composite film-forming agent is adjusted. By increasing the proportion of hydroxyl-modified acrylic emulsion, the density and wear resistance of the film layer after the sizing agent is formed are optimized.
[0032] Example 3:
[0033] This embodiment provides a high-adhesion glass fiber impregnating agent, the specific components by mass percentage are as follows: waterborne polyurethane emulsion 14.67%, hydroxyl-modified acrylic emulsion 7.33%, aminosilane coupling agent 2.89%, epoxy-based silane coupling agent 1.61%, modified nano-silica filler 1.2%, composite wetting and dispersing agent 0.8%, defoamer 0.18%, preservative 0.1%, and deionized water 71.32%, the total mass percentage of all components is 100%.
[0034] The preparation process parameters in this embodiment are completely consistent with those in Example 2, except that the ratio of the composite silane coupling agent is adjusted to increase the crosslinking ratio of epoxy silane and enhance the bidirectional bonding effect between the glass fiber and the resin matrix.
[0035] Example 4:
[0036] This embodiment provides a high-adhesion glass fiber impregnating agent. The components, by mass percentage, are as follows: 14.67% aqueous polyurethane emulsion, 7.33% hydroxyl-modified acrylic emulsion, 2.89% aminosilane coupling agent, 1.61% epoxysilane coupling agent, 2.1% modified nano-silica filler, 0.8% composite wetting and dispersing agent, 0.18% defoamer, 0.1% preservative, and 70.42% deionized water. The total mass percentage of all components is 100%.
[0037] The preparation process parameters in this embodiment are completely consistent with those in Example 3, except that the amount of modified nano-silica filler added is increased to maximize the repair of micro-defects in the film layer and enhance the film layer density and overall weather resistance.
[0038] Example 5:
[0039] This embodiment provides a high-adhesion glass fiber impregnating agent. The components, by mass percentage, are as follows: 4.74% aqueous polyurethane emulsion, 5.26% hydroxyl-modified acrylic emulsion, 0.74% aminosilane coupling agent, 1.06% epoxysilane coupling agent, 0.5% modified nano-silica filler, 0.3% composite wetting and dispersing agent, 0.08% defoamer, 0.05% preservative, and 81.57% deionized water. The total mass percentage of all components is 100%.
[0040] The preparation process parameters were set as follows: water bath constant temperature 38℃, base liquid stirring speed 340r / min, stirring time 6min, nanofiller high-speed dispersion speed 610r / min, dispersion time 18min, composite silane coupling agent dropwise addition time 10min, constant temperature activation stirring 35min, film-forming agent dropwise stirring speed 340r / min, stirring time 30min, and maturation time 2h.
[0041] Comparative Example 1: This comparative example was set as a single film-forming blank system. The components were as follows by mass percentage: 18.5% aqueous polyurethane emulsion and 81.5% deionized water, with a total mass percentage of 100%. No composite coupling agent, nanofiller, or composite wetting agent was added to the system. The rest of the preparation process and curing parameters were consistent with those of Example 1, in order to verify the synergistic effect of the composite coupling system and the nanofiller system.
[0042] Comparative Example 2: This comparative example was set as a single coupling agent system. The components, by mass percentage, were: 11.1% aqueous polyurethane emulsion, 7.4% hydroxyl-modified acrylic emulsion, 3.2% aminosilane coupling agent, 1.2% modified nano-silica filler, 0.8% composite wetting and dispersing agent, 0.18% defoamer, 0.1% preservative, and 75.12% deionized water, with a total mass percentage of 100%. Based on the basic formulation of Example 1, the epoxy silane coupling agent was removed, and only the single aminosilane coupling agent was retained, with the total amount of coupling agent remaining unchanged at 3.2%. The proportions of the remaining components and the preparation process parameters were completely consistent with Example 1, used to verify the synergistic advantages of bidirectional bonding of bissilanes.
[0043] Comparative Example 3: This comparative example uses a mainstream commercial glass fiber impregnating agent as a reference sample for existing technology. This product is prepared by physical compounding of a single acrylic film-forming agent, a single type of silane coupling agent and conventional inorganic fillers, and is processed by conventional industrial one-time mixing process.
[0044] Comparative Example 4: This comparative example uses the exact same raw materials as the present invention, but abandons the stepwise activation process specific to the present invention and uses a conventional one-time mixing process in the art. The component ratio is selected from the parameters of Example 1, and the rest of the production environment and test standards are consistent with the present invention, in order to verify the necessity of the coupling and synergy between the specific stepwise process and the component system.
[0045] All raw materials used in this invention are commercially produced industrially, with clearly defined parameters, open procurement channels, and no proprietary or confidential materials. Those skilled in the art can obtain these materials through open procurement from reputable chemical raw material companies. The specific models, key physicochemical properties, and acquisition methods of each raw material are as follows: The waterborne polyurethane emulsion is an industrial-grade anionic waterborne polyurethane film-forming emulsion, specifically model PU-218, with a solid content controlled at 30%-35% and a pH value of 7.0-8.0. It is a milky white and uniform emulsion at room temperature with no solvent residue, suitable for waterborne wetting systems for glass fibers, and can be directly purchased from domestic waterborne polymer material manufacturers. Hydroxyl-modified acrylic emulsion, specifically model AC-808 hydroxyl-modified acrylic copolymer emulsion, has a solid content of 40%-45%, a glass transition temperature of -10℃-0℃, and contains active hydroxyl functional groups. It can achieve film formation at room temperature and cross-linking and curing at high temperature, providing a dense film-forming substrate for wetting agents. It can be purchased in bulk by coating additive companies on the market. γ-aminopropyltriethoxysilane (aminosilane coupling agent), using industrial grade KH-550, with a purity ≥98%, is a colorless and transparent liquid that can be directly hydrolyzed to generate silanol groups, achieving chemical bonding with the inorganic surface of glass fibers. It is a common standard raw material in the field of glass fiber additives and has a wide range of procurement channels. γ-glycidyl etheroxypropyltrimethoxysilane (epoxysilane coupling agent), industrial grade KH-560, with a purity ≥98%, is a colorless and transparent liquid with moderate hydrolytic activity. It can undergo ring-opening crosslinking reaction with the active groups of the resin matrix and is a commonly used silane modification additive on the market. Modified nano-silica, using hydrophilic silane-modified nano-silica powder, with a particle size range of 20nm-80nm and a specific surface area of 120m². 2 / g-150m 2 / g, the powder is non-agglomerated and has excellent water dispersibility. Model VK-SP30 can be purchased directly from nanopowder material companies and can be used directly without secondary modification. The composite wetting and dispersing agent is physically compounded from a 1:1 mass ratio of polyether nonionic surfactant (model PE-100) and carboxylic acid anionic dispersant (model DA-20). Both are general-purpose wetting and dispersing aids for water-based systems, possessing excellent powder dispersion and emulsion compatibility, and have complete commercial channels. The polyether defoamer is XP-100, a special defoamer for water-based systems. It is suitable for weakly neutral water-based emulsion systems, and has a long-lasting foam suppression and defoaming effect without affecting the film-forming and adhesion properties of the system. Isothiazolinone preservative, using CMIT / MIT composite water-based preservative, with an active ingredient content of 1.5%, no formaldehyde release, suitable for long-term storage and preservation needs of water-based additives. Deionized water is prepared using conventional industrial reverse osmosis pure water equipment. It has a room temperature conductivity of ≤20μS / cm, is free of impurities and ion residues, and meets the industrial water standards for the preparation of water-based wetting agents. It can be prepared in-house or purchased commercially.
[0046] All of the above raw materials require no special pretreatment or artificial synthesis. They can be used directly by measuring and adding them according to the formula. The source of the raw materials is public, the parameters are fixed, and they can be completely replicated.
[0047] The specific operations of each step in the stepwise progressive emulsification and activation process described in this invention are as follows: Base solution preparation: Deionized water is added to the reaction vessel as the base material, and the water bath is kept at a constant temperature until the set temperature is reached. The stirring device is then turned on. Additive pre-dispersion treatment: Add the composite wetting and dispersing agent, defoamer and preservative to the base liquid in sequence, and stir continuously until each additive is completely and evenly dispersed; Uniform dispersion of nanoparticles: Modified nano-silica is added to a uniformly dispersed additive system and dispersed at high speed until the powder is free of agglomeration and the system is homogeneous; Stepwise hydrolysis and activation of coupling agent: First, slowly add aminosilane coupling agent to the system. After the addition is complete, stir at a constant temperature to activate. Then, slowly add epoxysilane coupling agent and continue stirring at a constant temperature until the coupling agent is completely hydrolyzed and activated. Low-temperature and low-speed composite emulsification of film-forming agents: Waterborne polyurethane emulsion and hydroxyl-modified acrylic emulsion are added dropwise to the activated system in sequence, and the mixture is stirred at low temperature and low speed until the two film-forming emulsions are completely composite emulsified. Blending, Filtration and Maturation: The composite emulsified system is stirred and blended, filtered to remove mechanical impurities, and then sealed and allowed to stand and mature until the system is stable.
[0048] Performance testing and results analysis: Test standards and sample conditions: In this test, alkali-free glass fiber filaments were used as the treatment substrate. The sizing rate of all samples was uniformly controlled at 1.3% to eliminate the influence of sizing rate fluctuations on the test results. After the sizing agent was applied, all samples were uniformly dried and cured at 125℃ for 15 minutes before various performance tests were carried out.
[0049] Five parallel tests were conducted on each group of samples, and the final test result was the arithmetic mean of the five test data to ensure that the test data was accurate, reliable and reproducible.
[0050] The interfacial shear strength test was performed in accordance with ASTM D2344, and the surface adhesion grade test was performed in accordance with GB / T 9286.
[0051] The test environment for resistance to damp heat aging was set at 85℃ and 85% relative humidity, with a continuous aging time of 200h. The retention rate of mechanical strength of the sample after aging was then tested.
[0052] Film uniformity was assessed by optical microscopy. Storage stability was tested by sealing the sample at room temperature for 90 days and observing whether stratification or precipitation occurred.
[0053] The wear resistance was tested using a reciprocating friction test, recording the number of friction cycles at which the glass fiber sample broke.
[0054] The performance test results are shown in Table 1 below:
[0055] Results analysis: The interfacial shear strength of each embodiment of the present invention is significantly higher than that of existing commercial products and conventional combined modified products. Among them, the interfacial shear strength of the best-performing embodiment 4 reaches 80.2 MPa, which is more than 30% higher than that of traditional commercial wetting agent products, and the interfacial adhesion strengthening effect is very outstanding.
[0056] Most embodiments of the present invention achieve the highest industry standard of Grade 0 in adhesion, with only Embodiment 5, which has a low component addition, achieving Grade 1 in adhesion. Overall, the adhesion performance is excellent, enabling close bonding between the glass fiber and the resin matrix and effectively avoiding the problem of interface detachment during the use of composite materials.
[0057] Regarding resistance to damp heat aging, the strength retention rate of all embodiments of the present invention remained consistently above 92% during damp heat aging, with the optimal embodiment achieving a strength retention rate of 97.5%. Compared with the comparative products, the product of the present invention exhibits stronger aging resistance stability, and can maintain the interfacial bonding structure and film integrity for a long time in complex service environments with high temperature and high humidity of 85℃ and 85%RH, effectively delaying the degradation of the mechanical properties of the composite material and significantly extending the service life of the product.
[0058] In terms of film-forming performance and wear resistance, the product of this invention exhibits good film uniformity, with no obvious defects such as pores or cracks in the film layer, and a significant improvement in the number of wear-resistant fractures. This demonstrates that the proprietary formula and matching preparation process of this invention can form a uniform, dense, and highly tough protective film layer on the surface of glass fiber through multi-level synergistic effects, significantly improving the wear resistance of glass fiber during weaving, composite molding, and use.
[0059] Regarding storage stability, after 90 days of sealed storage at room temperature, all products of the present invention maintained a uniform and transparent state, with no stratification, no precipitation, and no flocculation, demonstrating excellent storage stability.
[0060] Under the same storage conditions, all comparative products exhibited varying degrees of stratification or precipitation problems, fully demonstrating that the component compatibility and overall stability of the formulation system of this invention are far superior to existing conventional wetting agent systems.
[0061] Example 5 with low addition amount significantly reduces the cost of raw materials, while still having a comprehensive performance that far exceeds that of existing commercial products. Thanks to the efficient synergistic effect of the system of the present invention, it breaks the inherent industry rule that film formation is incomplete and performance is greatly reduced when the addition amount of conventional wetting agent is low. It achieves an effective balance between low-cost preparation and high-performance output, and is suitable for the needs of industrial low-cost and large-scale production.
[0062] The performance defects of Comparative Example 1 and Comparative Example 2 directly prove that a single film-forming system or a single coupling system cannot achieve simultaneous optimization of multiple properties. The absence of any set of functional components will cause a significant decrease in interfacial bonding, film quality, and weather resistance, which intuitively confirms the necessity of multi-level component synergy in composite film formation, bidirectional bonding, and nanofilling.
[0063] The test data of Comparative Example 4 show that when the raw materials of the present invention are used in their entirety and the proprietary step-by-step preparation process is abandoned, the components cannot achieve orderly activation and uniform compounding, the synergistic effect between the components cannot be effectively activated, the various performances of the product are greatly reduced and the stability of the system deteriorates. This fully demonstrates that the coupling and synergy between the component system and the proprietary process is the core key to achieving the excellent performance of the present invention. The combination of the two is irreplaceable and cannot be achieved by simply adding raw materials or adjusting conventional processes in this field.
[0064] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention.
Claims
1. A high-adhesion glass fiber impregnating agent, characterized in that, It is composed of the following components by mass percentage: waterborne polyurethane emulsion 11.1%-14.67%, hydroxyl-modified acrylic emulsion 7.33%-7.4%, aminosilane coupling agent 1.75%-2.89%, epoxysilane coupling agent 1.45%-1.61%, modified nano-silica 1.2%-2.1%, composite wetting and dispersing agent 0.3%-0.8%, defoamer 0.08%-0.18%, preservative 0.05%-0.1%, and deionized water 70.42%-81.57%, with the total mass percentage of all components being 100%. The aqueous polyurethane emulsion is an industrial-grade anionic aqueous polyurethane film-forming emulsion with a solid content of 30%-35%; the hydroxyl-modified acrylic emulsion is an industrial-grade hydroxyl-containing acrylic copolymer emulsion with a solid content of 40%-45%; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the epoxysilane coupling agent is γ-glycidoxypropyltrimethoxysilane; and the modified nano-silica is a hydrophilic silane surface-modified powder with a particle size of 20nm-80nm. The composite wetting and dispersing agent is formulated from polyether nonionic surfactants and carboxylic acid anionic dispersants; the defoamer is a polyether defoamer specifically for water-based systems; the preservative is an isothiazolinone preservative specifically for water-based coatings; and the conductivity of the deionized water is not higher than 20 μS / cm.
2. A method for preparing a high-adhesion glass fiber impregnating agent, characterized in that, The preparation of the high-adhesion glass fiber sizing agent according to claim 1 includes the following steps performed in sequence: preparation of base liquid, pre-dispersion treatment of additives, uniform dispersion of nanoparticles, stepwise hydrolysis and activation of coupling agent, low-temperature and low-speed composite emulsification of film-forming agent, and blending, filtration and maturation. The base solution was prepared by adding deionized water to the reaction vessel, maintaining a constant temperature of 38℃-40℃ in a water bath, stirring at a speed of 340r / min-380r / min, and stirring for 6min. The pre-dispersion treatment of the additives involves sequentially adding a composite wetting and dispersing agent, an antifoaming agent, and a preservative to the base liquid, and stirring until the dispersion is uniform. The nanopowder is uniformly dispersed as follows: Modified nano-silica is added to the system, the dispersion speed is 610 r / min-680 r / min, the dispersion time is 18 min, and the high-speed dispersion is carried out until the powder is uniform and free of agglomeration. The coupling agent is activated by stepwise hydrolysis: first, aminosilane coupling agent is added dropwise and stirred for activation; then, epoxysilane coupling agent is added dropwise and stirred at a constant temperature for activation. The total dropwise addition time of the coupling agent is 10 min, and the constant temperature activation stirring time is 35 min. The film-forming agent is subjected to low-temperature and low-speed composite emulsification: water-based polyurethane emulsion and hydroxyl-modified acrylic emulsion are added dropwise to the system in sequence, the stirring speed is 340r / min-380r / min, the stirring time is 30min, and the low-temperature and low-speed stirring is carried out until the composite emulsification is complete. The blending, filtration, and maturation process involves stirring and blending the system, filtering it, sealing it, and allowing it to stand for maturation for 2 hours.
Citation Information
Patent Citations
Glass fiber impregnating compound, preparation method thereof, glass fiber product and application
CN114853365A
Preparation and application of water-based two-component high-adhesion solid-color paint
CN115960499A